ANALISIS PENGARUH JARAK DAN KECEPATAN TERHADAP KINERJA SISTEM KOMUNIKASI ANTAR KENDARAAN BERBASIS NRF24L01 - I Md. Anggar Dwi A, I Md. Anggar Dwi A; Indra ER, Ngurah; Pramaita, Nyoman (Program Studi Teknik Elektro UNUD, 2024)
The study investigates the impact of distance and speed on wireless communication networks, on vehicle-to-vehicle communication using the low-cost module NRF24L01. Evaluation of performance indicators, such as latency and data loss, is carried out to determine the impact of both of these factors. Understanding the impact of distance and speed on wireless networks is vital as dynamic vehicle-to-vehicle communication develops. The study used several evaluation variations, including measurements ranging from 5 to 100 metres in a stationary scenario, as well as additional tests performed in moving conditions. The test results can provide insight into the advancement of intelligent transportation systems, improving safety, efficiency, and general communication in vehicle-to-vehicle interaction. This will optimize the implementation of the end result of the technology generated by the parties involved.